sqrt (-48) = sqrt ( -16 x 3)
= sqrt ( -1 x 16 x 3)
Calculate for the square roots of the factors.
= sqrt (-1) x 4 x sqrt (3)
The square root of -1 may also be written as i which means that the value is imaginary. Thus, the final answer would be,
= 4i (sqrt 3)
The answer is C
Do you need it in a different form than that?
i² = -1 by definition.
given that there are two triangles j'k'l' and jkl>
the former is got by dilating the second one.
when drawn on a grid, (graph paper) coordinates of vertices of first triangle is
(6,12)j, (9,6)k and (12,9)l
side jk has length = distance between j and k
side j'k'=distance between j' and k'
ie j'k'l' has sides 1/3 of that of corresponding sides of jkl.
hence scale factor of 1/3 is used to get j'k'l'from jkl